For what endpoint does myocardial 123I-MIBG scintigraphy have the greatest prognostic value in patients with chronic heart failure? Results of a pooled individual patient data meta-analysis. (1st September 2014) - Verschure, Derk O.; Veltman, Caroline E.; Manrique, Alain; Somsen, G. Aernout; Koutelou, Maria; Katsikis, Athanasios; Agostini, Denis; Gerson, Myron C.; van Eck-Smit, Berthe L.F.; Scholte, Arthur J.H.A.; Jacobson, Arnold F.; Verberne, Hein J.
Abstract: Aims: The purpose of this study was to determine the most appropriate prognostic endpoint for myocardial 123 I-metaiodobenzylguanidine (MIBG) scintigraphy in patients with chronic heart failure (CHF) based on aggregate results from multiple studies published in the past decade. Methods and results: Original individual late (3–5 h) heart/mediastinum (H/M) ratio data of 636 CHF patients were retrieved from six studies from Europe and the USA. All-cause mortality, cardiac mortality, arrhythmic events, and heart transplantation were investigated to determine which provided the strongest prognostic significance for the MIBG imaging data. The majority of patients was male (78%), had a decreased left ventricular ejection fraction (31.1 ± 12.5%), and a mean late H/M of 1.67 ± 0.47. During follow-up (mean 36.9 ± 20.1 months), there were 83 deaths, 67 cardiac deaths, 33 arrhythmic events, and 56 heart transplants. In univariate regression analysis, late H/M was a significant predictor of all event categories, but lowest hazard ratios (HRs) were for the composite endpoint of any event (HR = 0.30, 95% CI 0.19–0.46), all-cause (HR = 0.29, 95% CI 0.16–0.53), and cardiac mortality (HR = 0.28, 95% CI 0.14–0.55). In multivariate analysis, late H/M was an independent predictor for all event categories, except for arrhythmias. Conclusions: This pooled individual patient data meta-analysis showed that, in CHF patients, the late H/M ratio is not only useful as a dichotomous predictor of events (high vs. low risk), but also has prognostic implication over the full range of the outcome value for all event categories except arrhythmias.